Implementing Competency-Based Language Teaching Assessment and Achievement of Competency in Speaking Skills at Grade Four - Derseh Gebisa Ayana; Ahmed Sherif Ali; Warabu Rufael Disasa (Sciendo, 2024)
The study aimed to investigate the implementation of Competency-Based Language Teaching assessment and proficiency in English speaking skills.